Proposta de organização de estoque: estudo de caso em uma distribuidora de bebidas - GONÇALVES, Adriane Sacramento (2019)
This work aimed to propose a reorganization of the storage process in the warehouse of the company under study, using the quality tools to improve these processes. In order to analyze the company's stock, a survey of data was carried out along with the company's archives, collection of information from the manager and stockist, as well as on-site observation. The ABC Curve, 5S Program and the 5W1H quality tool were used to elaborate the proposal of stock organization. The collection of data from those responsible allowed an analysis of the current situation of the stock, so that it could verify at which points can be applied the tools to improve the stock. From this, the products were classified by the ABC curve method. Therefore, it was proposed to apply the 5S Program to organize the stock, applying it through Action Plan 5W1H and using as an auxiliary tool the FEFO Method for withdrawal of products. The tools used to prepare the proposals proved to be very effective, as they fulfilled the proposed objective.